Observation of the new emission line at ~3.5 keV in X-ray spectra of galaxies and galaxy clusters - Iakubovskyi, D.A. (Advances in Astronomy and Space Physics, 2016)
The detection of an unidentified emission line in the X-ray spectra of cosmic objects would be a `smoking gun'signature for the particle physics beyond the Standard Model. More than a decade of its extensive searches results in several narrow faint emission lines reported at 3.5, 8.7, 9.4 and 10.1 keV. The most promising of them is the emission line at ∼3.5 keV reported in spectra of several nearby galaxies and galaxy lusters. Here I summarize its up-to-date status, overview its possible interpretations, including an intriguing connection with the radiatively decaying dark matter, and outline future directions for its studies.